Scandium-Catalyzed Intramolecular Friedel–Crafts Reactions of 2-[(2-Alkyl-1H-indol-3-yl)methylene]malonates - Oh, Chang Ho; Park, Hyo Seung; Park, Nari; Kim, So Young; Piao, Lanhua (Synlett, 2014)
We have synthesized a variety of 2-[(2-alkyl-1H-indol-3-yl)methylene]malonates and studied their scandium-catalyzed intramolecular Friedel–Crafts reactions leading to the corresponding polycyclic compounds such as indeno[1,2-b]indoles and benzo[1,2-b]carbazoles.
Keywords: scandium triflate; indole; Friedel–Crafts reaction; carbazole; polycycle